Pergeseran Isu dalam Wacana Desa Tangguh Bencana (DESTANA) Pandemi Covid-19: Kasus Yogyakarta dan Surabaya - Muhamad Sulhan (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2021)
This article aims to describe complexity of news texts on discourse Desa Tangguh Bencana (Destana) in Yogyakarta and Surabaya which are contained in online media throughout the process of handling the Covid-19 pandemic in 2020. This article use the critical discourse analysis (CDA) from Teun A van Dijk’s model (1988) to analyze the structure of news report which consists of two main categories: summary and story. The summary aspect is reduced to an analysis of headlines and leads. The story is revealed to analysis of the situation and comments. The result of analysis found that had been a shift in Destana discourse in 2 (two) online media (merdeka.com, and medcom.id3). The discourse shitfting comes from an informative discourse to an investigative discourse during May – November 2020. Another finding was that there was a pattern of the use of issues and discourses that remain the same as a 'stage' for the appearance of the political elite. They have been using Destana's humanist discourse to become politically charged with the shift in the word 'Desa' into 'Kampung'.